TiungLap: A Quadcopter Drone for Window Cleaning with an Integrated Pressure Washer Tethering System - Ahmad Fathan Fadzulli; Omar Mohd Faizan Marwah; Mohammad Zulafif Rahim; Siti Juita Mastura Salleh; Zamri Omar; Suhaimi Hassan; Reazul Haq Abdul Haq (International Journal of Integrated Engineering, 2025)
The TiungLap drone, developed to address the high risks and inefficiencies associated with traditional high-rise window cleaning, integrates a tethered high-pressure washer system to improve safety and operational time. The drone features advanced GPS navigation, real-time monitoring, and LiDAR-based obstacle avoidance for precise cleaning in complex environments. The objective of this study was to optimize the thrust, power consumption, and control stability of the drone during cleaning operations. Utilizing four X9 motors, the drone achieved a maximum thrust of 21.23 kgf per motor, ensuring sufficient lift to handle its 22 kg payload. Power analysis revealed the motors consumed 4790.2W each, contributing to a total system power consumption of 7421.25W. A key challenge was stabilizing the drone under the influence of external forces from the tethered hose, which was addressed through manual tuning of the PID controller. This tuning reduced roll error by 94.9% and pitch error by 87.8%, significantly improving drone stability. Future research should focus on enhancing flight endurance and further optimizing control algorithms to handle external forces more effectively.